Influence of Animated Video Media on the Knowledge and Attitudes of Fluor Albus Prevention for Young Women at SMP PGRI 2 Ciledug - Moshthafavi, Alfi Zahra; Mardhiati, Retno (Jurnal Pendidikan Kesehatan, 2024)
Cases of fluor albus are still common in women and if not addressed will lead to infection of the female genital area. Adolescent need to be educated in such a way, because education has an impact on long-term decisions. The existence of this study is to see the effect of fluor albus prevention education counseling using animated videos on the knowledge and attitudes of young women at SMP PGRI 2 Ciledug in 2023. This study applied a quantitative method of experimental design with non-randomised pre-test post-test control group design and non-probabilty sampling technique with purposive sampling. A total of 110 grade 9 young women were sampled. Wilcoxon and Mann-Whitney test were used as analysis techniques. There was a significant difference in the mean total score of pre-test (6,55) and post-test (8,82) of knowledge variables of the experimental group (p-value <0,00001). A significant difference was also found in the mean total score of pre-test (4,78) and post-test (7,69) attitude variables in the same group. There was a significant difference in the mean total score of the experimental groups’s knowledge post-test (8,82) with the control (6,84) and the mean total score of the experimental group’s attitude post-test (7,69) with the control (4,64). This happened because only the experimental group was exposed to education, so that the reasoning was that providing education using animated video media had an influence on the difference in the total score of knowledge and attitudes of young women at SMP PGRI 2 Ciledug